Bivalent non-human gal-α1-3-gal glycan epitopes in the Fc region of a monoclonal antibody model can be recognized by anti-Gal-α1-3-Gal IgE antibodies - Grayson Hatfield; Lioudmila Tepliakova; Jessica Tran; Huixin Lu; Michel Gilbert; Roger Y. Tam (Taylor & Francis Group, 2023)
ABSTRACTMonoclonal antibody (mAb) production using non-human cells can introduce non-human glycan epitopes including terminal galactosyl-α1-3-galactose (α1-3-Gal) moieties. Cetuximab is a commercial mAb associated with causing anaphylaxis in some patients due to the binding of endogenous anti-α1-3-Gal IgE to the Fab (containing bi-α1-3-galactosylated glycans) but not to the Fc region (containing mono-α1-3-galactosylated glycans). Despite being low in abundance in typical commercial mAbs, the inherent sensitivity of cell culture conditions on glycosylation profiles, and the development of novel glycoengineering strategies, novel antibody-based modalities, and biosimilars by various manufacturers with varying procedures, necessitates a better understanding of the structural requirements for anti-α1-3-Gal IgE binding to the Fc region. Herein, we synthesized mAb glycoforms with varying degrees and regioisomers of α1-3-galactosylation and tested their binding to two commercial anti-α1-3-Gal human IgE antibodies derived from a human patient with allergies to red meat (comprising α1-3-Gal epitopes), as well as to the FcγRIIIA receptor. Our results demonstrate that unexpectedly, anti-α1-3-Gal human IgE antibodies can bind to Fc glycans, with bi-α1-3-galactosylation being the most important factor, highlighting that their presence in the Fc region may be considered as a potential critical quality attribute, particularly when using novel platforms in mAb-based biotherapeutics.